2014
DOI: 10.3896/ibra.1.53.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Colony development of two Carniolan genotypes (Apis mellifera carnica) in relation to environment

Abstract: SummaryThe objective of this study was to compare the colony development cycle (unsealed and sealed worker brood, drone brood, pollen and colony strength) of two Apis mellifera carnica subpopulations in two distinct environments (alpine and continental). At each test location were two sub groups of 12 colonies headed by naturally mated sister queens from either the Institute of Apiculture Lunz am See, Austria (AT) or from the Faculty of Agriculture University of Zagreb, Croatia (HR). Colony development was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This could indicate a maladaptation to the local environmental conditions in our study area, where the flowering periods of plants start a few weeks earlier than in Germany, from where these queens originated. A similar phenomenon was observed by Dražić et al (2014) who reported that in Croatia colonies headed by queens from Austria reared less brood during spring compared to the local colonies. The significantly smaller number of bees and brood cells observed in the NS group could be the consequence of its origin.…”
Section: Discussionsupporting
confidence: 84%
“…This could indicate a maladaptation to the local environmental conditions in our study area, where the flowering periods of plants start a few weeks earlier than in Germany, from where these queens originated. A similar phenomenon was observed by Dražić et al (2014) who reported that in Croatia colonies headed by queens from Austria reared less brood during spring compared to the local colonies. The significantly smaller number of bees and brood cells observed in the NS group could be the consequence of its origin.…”
Section: Discussionsupporting
confidence: 84%
“…Two more recent studies within Italian honey bee populations [18] and two Carniolan strains [19] supported the presence of G Â E for colony development traits.…”
Section: Box 1 Genotype-environment Interactions (G • E)mentioning
confidence: 78%
“…Numerous surveys and experimental studies have identified the invasive parasitic mite Varroa destructor (hereafter referred to as Varroa) as the most prominent factor affecting honey bee health and contributing to colony losses, both in Europe and worldwide [16,[19][20][21]. Reports of honey bee populations which survive without any Varroa treatment are known from the literature, resulting from selection in both natural and experimental situations [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the POM approach, statistical analyses is not strictly required for model evaluation; however, the model outputs could be compared with other independent data available in the literature (e.g. Rueppell et al (2007) for lifespan and AFF and Hatjina et al (2014) and Dražić et al (2014) for colony development).…”
Section: Have the Performance Criteria For The Model Been Predefined mentioning
confidence: 99%
“…The model outputs should be compared with other independent data where information on the environmental conditions of the experiments is available (e.g. Rueppell et al (2007) for lifespan and AFF and Hatjina et al (2014) and Dražić et al (2014) for colony development). In order to validate the model at the European level, the model outputs should be compared with data obtained under different environmental conditions representative of the three EU regulatory zones.…”
Section: Has the Performance Of The Model Been Reported In An Objectimentioning
confidence: 99%